Coaching-Based Academic Supervision to Improve Teacher Performance in Implementing Differentiation Learning at SDN 014 Kempas Jaya - Nawas, Abu (Perspektif Pendidikan dan Keguruan, 2023)
This study describes the supervision of the principal to improve teacher performance in implementing differentiated learning. This research is a descriptive qualitative research with pedagogical, sociological, and managerial approaches. This research was conducted at SDN 014 Kempas Jaya. Data sources are primary data and secondary data. Data collection techniques using observation, interviews, and documentation. The research instruments are interview guides, observation sheets and documentation. Data were analyzed by data reduction, data presentation, and drawing conclusions. Testing the validity of the data is done through technical triangulation and source triangulation. The results showed that the coaching - based supervision model could improve teacher performance in implementing differentiated learning. The stages of the supervision stage are the planning stage, including socialization, explaining the supervision indicators and preparing the schedule, the implementation stage covering the intention, pre-supervision, supervision and post-supervision activities. Obstacles to the implementation of supervision are the broad managerial scope of the principal; teachers are not ready to be supervised, frequent changes of principals, limited infrastructure, and lack of teacher discipline.